Konsep Pengatur Lalu-Lintas Sinkron Adaptif Kepadatan Untuk Solusi Minimalisasi Durasi Waktu Tunggu Kendaraan - Kurniawan, Freddy; Al Hasibi, Rahmat Adiprasetya (Jurnal Semesta Teknika, 2007)
To minimize travel time in a highway, some traffic controllers must be synchronized to the other. Intersection controllers of an area are interconnected with a communication network through which synchronization information is exchanged. The main purpose of synchronized traffic control system is to minimize the waiting time of almost all vehicles in each traffic light. Green and duration time of all traffic control system are derived from some parameters such as adjacent green time, vehicle speed and acceleration, and estimation of travel time. Â